Earth's Crust and Its Evolution From Pangea to the Present Continents - Cengiz, Mualla; Karabulut, Savaş (IntechOpen, 2022)
Despite decades of study, fundamental aspects of the development of the Earth's crust remain enigmatic. This book presents geophysical and geological studies obtained from different tectonic structures and geological time intervals. It contains three sections: "Crustal Evolution and Tectonic Problems", "Geophysical Methods in Geological Applications" and "Seismic Forecasting, Seismotectonics and Geodynamic Evolution of the Himalayan Belt". Chapters address such topics as the evolution of tectonic structures of Earth, how geophysical and geological data can be used for modelling this evolution, and the geodynamic processes in the Earth's crust with the present tectonic activity.